Patient co-responsibility in the treatment process in the light of coordinated care – Polish experiences - Sabina Karczmarz; Magdalena Bogdan; Aneta Nitsch-Osuch; Anna Owczarczyk; Paweł Żuk; Sergii Burma; Leszek Warsz; Kamil Krzysztof Cołoś (Family Medicine & Primary Care Review)
The patient’s co-responsibility for the treatment process is strongly related to the patient’s lifestyle and health attitudes. Lifestyle determines human health through interrelated behaviors, customs and habits that may influence the level of risk of premature development of diseases. To identify unhealthy behaviors and prevent their health consequences, a comprehensive lifestyle assessment is necessary. The aim of the research presented in the article was to analyze and assess the role of the primary healthcare team in shaping a healthy lifestyle and patient attitudes, as well as to analyze the possibilities of shaping patient attitudes by medical staff through new solutions and the implementation of coordinated care. The research methodology was based on a review of available source literature. Scientific articles on the research topic were selected using the following keywords in two electronic databases (PubMed and Scopus): coordinated care, patient responsibility, lifestyle, healthy attitude and primary health care. The study analyzed lifestyle as a factor influencing health and health-promoting behaviors of Polish society. Based on the analysis, it was concluded that the role of coordinated health care in shaping patient co-responsibility, including a healthy lifestyle and attitudes among patients, is very important and the healthcare model based on coordinated care should be patient-focused, use preventive measures and respond to contemporary challenges in the health sector.